STUDY OF THE ABBOT'S ROLE IN CREATING STRENGTH TO THE COMMUNITY: A CASE STUDY OF THE ABBOT RULING AREA OF REGIONAL SANGHA 2 - Maungseang, Santi (Journal of MCU Social Science Review, 2019)
The aims and objectives of the research topic (1) To study the duty and the prosperity of Community on the role of the ecclesiastical monk in monastical section II (2) to study the process of strength of community on the role of the ecclesiastical monk in monastical section II) (3) to integrate the main Dhamma of strength of community on the role of the ecclesiastical monk in monastical section II Methodology was the Mixed method between the qualitative research collected data from document, In - depth interviews and focus group discussion from key informants, and the quantitative research collected data from Questionnaire Findings of this research were as follows: ecclesiastical monk in monastical section II had the role Strength of Community following by the rule (P.R.B.) of sixth sections of monk in perfection. They had the role in the society, Economy, Selfreliance, Moral and ethical conduct, culture, good health, Conservation of natural resources, and environment of Community. The plan of ecclesiastical monk in monastical action II, it consists of three main development, as following: To create the example for community such as: He must be the dependence on action, word and mind of people to eradicate from social suffering to happy life.he must help people on giving the good consolation, to improve the resolution of human issues. Collaboration of community such as: he would be the Collaboration with community on the exhibition dealing with the important days.Supporting on the social activities such as: The community would have the privilege to make itself the decision and to have the technique on its decision that it deals with the public activities and advantage for the variety of the development.